Exercise after Breast Reconstruction Surgery: Evaluating Current Trends and Practices of U.S. Plastic Surgeons. Issue 10 (October 2021) - Alabaster, Kelsey; Homsy, Christopher; Puyana, Salomon; Higgins, Margaret; Ferrin, Peter; Mulcahey, Mary K.; Chaffin, Abigail
Abstract : Background: Breast cancer patients have reported restricted mobility, pain, lymphedema, and impaired sensation and strength after breast reconstruction surgery. Many studies have demonstrated benefits of early exercise intervention (within the first 2 weeks) for functional recovery after breast surgery. From the surgeon's perspective, there is a concern that early postoperative exercise can potentially lead to complications or even reconstruction failure. The purpose of this study was to evaluate current trends and practices related to patient exercise after breast reconstruction among plastic surgeons in the United States. Methods: An anonymous, electronic survey was sent to a random cohort of 2336 active members of the American Society of Plastic Surgeons. The survey consisted of 23 questions and was used to assess how plastic surgeons currently manage patients postoperatively after breast reconstruction. Results: Responses were received from 228 plastic surgeons. Thirty-six (18%) respondents reported never prescribing physical therapy (PT) postoperatively. In total, 154 (76%) prescribe PT to less than 50% of their patients, and those who do most commonly prescribe it more than 3 weeks postoperatively. There was no difference in perceived rate of complications by respondents who prescribe early versus late exercise ( χ 2 (5) = 8.815, P = 0.117). Conclusions: Based on our survey results, only a small percentage of plastic and reconstructive surgeons support early initiation of exercise, and PT is being prescribed to a minority of patients. Surgeons and physical therapists must work together to devise a recovery program that maximizes functional outcomes for patients while also limiting complications.